Treatment of depression in a low-income primary care setting with co-located mental health care - Uebelacker, Lisa A. (2009)
OBJECTIVE: To characterize depression treatment-as-usual in a large primary care practice in the U.S. with co-located mental health care, and to examine predictors of receiving any treatment and receiving adequate treatment. METHODS: Primary care patients were systematically approached in waiting rooms. Those with a minimum level of depression symptoms (n = 91) were asked to participate in a study in which they completed assessments of mental health service use, depression symptoms, and related problems. RESULTS: In this setting with co-located mental health care, most patients with elevated depressive symptoms were receiving some type of mental health care, indicating they had been identified as depressed. However, only half were receiving “minimally adequate care.” Minority patients were less likely to receive any care. Patients who were more depressed, demonstrated poorer problem-solving ability, and had poorer physical health were more likely to receive any treatment and to receive minimally adequate treatment for depression. CONCLUSION: Even in the context of co-located mental health care, there is still room for improving treatment of depressed patients. For some depressed patients, an important first step will be to ensure they are receiving minimally adequate care. However, others may need more intensive care, including combined treatments.